Pertumbuhan dan Keragaan Tanaman Jeruk Keprok Borneo Prima pada Dosis Pupuk dan Bentuk Pangkas Berbeda - Tiara Septirosya; Roedhy Poerwanto; Abdul Qadir (Jurnal Agroteknologi, 2017)
Borneo Prima Mandarin (Citrus reticulata cv Borneo Prima) is a new local commodity that grown in lowland but has an interesting orange skin. As a new commodity, Borneo Prima Mandarin has to be developed in order to reduce citrus import. The research was conducted in lowland area (250 m above sea level) IPB research station, Sindang Barang, Bogor from February 2014 to February 2015. The aim of this research was to observe the effect of phosphorus and potassium (PK) fertilizer and pruning on the growth and performance of the plants. This research used Randomize Complete Block Design (RCBD) with two factors. The first factor was aplication of PK fertilizer (15 g P+ 10 g K, 15 g P+ 15 g K, 20 g P+10 g K, 20 g P+15 g K per plant) and the second factor was pruning form (without pruning, open center pruning and hedge pruning). The result showed that the combination of phosporus and potassium fertilizer just gave a significant effect to number of shoot. The highest number of new shoots formed by fertilizing 15 g P+10 g K per tree per application. Pruning treatments had significant effect to plant architecture (i.e reduce plant height, land occupation). Open center pruning and hedge pruning made the crown more open that can increase the light interception so that increase the rate of photosynthesis.